Coping in African Americans With Inflammatory Bowel Disease: An Integrative Review of the Literature. (July 2019) - Scott, Patricia D.; Lockhart, Joan S.; Jakub, Karen E.; Zoucha, Rick; Nguyen, Geoffrey C.
Abstract : Given the chronic nature of inflammatory bowel disease, understanding the coping behaviors of individuals affected with the disease is important to influence health outcomes. Although minorities comprise a significant portion of individuals with the disease, little is known about the potential influence of one's culture, specifically among African Americans, on coping with inflammatory bowel disease. This integrative literature review examined the past decade of research related to the coping behaviors of African Americans living with inflammatory bowel disease to identify opportunities for further research. Five studies were identified via database searches of PubMed, PsychInfo, CINAHL, and the Cochrane Library and limited to studies published in English, full-text, peer-reviewed, and adult samples that included African Americans. Findings lacked information specific to coping in African Americans. Results were categorized by coping and disease activity, acquisition of knowledge, and personal coping. An association between poor coping behaviors and active disease was reported. The disease frequently hindered academic pursuits of college students, with increased knowledge about the disease associated with the use of better coping strategies. Personal coping behaviors were reported in stressful social situations, food choices, and religion. Results emphasized the need for future research to explore the influence of culture on the coping behaviors of African Americans with inflammatory bowel disease.